A DFT method analysis for formation of hydrogen rich gas from acetic acid by steam reforming process - Hossain, Md Arafat; Jewaratnam, Jegalakshimi; Ramalingam, Anantharaj; Sahu, Jaya Narayan; Ganesan, Poo Balan (Elsevier, 2018)
Quantum chemical calculation has been considered for molecular behaviour analysis during hydrogen production through steam reforming process of acetic acid is an organic compound and the simplest carboxylic acid. Hydrogen and also Carbon dioxide are the products when acetic acid reacts with water. Geometry optimization for individual molecules (CH3COOH, H2O, H2, and CO2) was carried out using DFT/B3LYP method in Gaussian 09 W computational chemistry program based on 6-31G(d) basis set along with the consideration of reactant side (two molecules together) and product side (two molecules together). Several fundamental features for optimized geometry such as bond angle, bond length and also the minimized energy values have been computed. The method has been compared with other literatures for validation. The nature of the chemical conversation in terms of electron flow, ionisation potential (I) and electron affinity (A) between acetic acid and water has been investigated via HOMO–LUMO energy values and gap. Interaction energies of reactant along with product side and some essential properties in quantum chemical application; chemical potential (μ), the global hardness (η) and softness (S), electrophilicity index (ω) as well as electronegativity (X) have also been calculated and analyzed.